Pericardial Effusion Following Drain Removal after Percutaneous Epicardial Access for an Electrophysiology Procedure. Issue 3 (13th January 2015) - KILLU, AMMAR M.; WAN, SIU‐HIN; MUNGER, THOMAS M.; HODGE, DAVID O.; MULPURU, SIVA; PACKER, DOUGLAS L.; ASIRVATHAM, SAMUEL J.; FRIEDMAN, PAUL A.
<x xml:space="preserve">Abstract</x> Objectives To determine the frequency and predictors of pericardial effusion following epicardial sheath removal. Background Pericardial effusion can occur following cardiac surgical or interventional procedures including percutaneous epicardial access (EpiAcc), which is increasingly used as part of electrophysiology ablation procedures. Methods A retrospective analysis of the Mayo Clinic comprehensive electronic medical record was performed from all patients who underwent planned EpiAcc as part of an electrophysiology ablation procedure between January 1, 2004 and June 30, 2013. Results Of 144 patients (mean age 51.3 ± 15.5 years, 68% male) who underwent planned EpiAcc as part of an electrophysiology ablation (95.8% pericardial access success rate), seven (4.9%) developed a postoperative pericardial effusion requiring repeat EpiAcc. Inferior access was utilized in 74 (51.4%) patients. Patients with pericardial effusion tended to be younger (41.1 years vs 51.8 years, P = 0.08) and were more likely to have undergone inferior approach access (85.7% vs 49.6%, P = 0.06) than those who did not develop postoperative pericardial effusion. Seventy‐one percent of patients with postoperative pericardial effusion versus 32.1% of patients without postoperative pericardial effusion had a preprocedure ejection fraction ≥55% (P = 0.03). There were no procedural‐related deaths, and no difference in mortality between groups. Conclusions Postoperative pericardial effusion requiring repeat access/drainage was relatively infrequent, occurring in 4.9% of patients shortly after epicardial procedures. While the majority occur early and therefore require close observation, some patients may present in a delayed manner.